PCl5 as a mild and efficient catalyst for the synthesis of bis(indolyl)methanes and di-bis(indolyl)methanes - Alireza Hasaninejad; Abdolkarim Zare; Hashem Sharghi; Reza Khalifeh; Ahmad Reza Moosavi Zare (Bulletin of the Chemical Society of Ethiopia, 2008)
Phosphorus pentachloride (PCl5) can efficiently catalyze the condensation of indoles with aldehydes as well as ketones at room temperature to afford bis(indolyl)methanes and di-bis(indolyl)methanes in high yields and short reaction times.